INFLUENCE SCHROTH EXERCISE ON DECREASING THE DEGREE OF SCOLIOSIS IN TEENAGERS :NARRATIVE REVIEW - Muslimah, Putri Ainiyyah; Khotimah, Siti (Sport and Fitness Journal; Vol 10 No 3 (2022): Volume 10, No.3, September 2022DO - 10.24843/spj.2022.v10.i03.p01, 2022)
Background: Scoliosis is a curvature of the spine caused by incorrect posture habits such as sitting and upright. For example. In the wrong sitting position or using a bag that is not correct with a posture will cause pain and can also cause the formation of a type C or S curve in the spine. The findings require many high-quality studies. Therefore, it was necessary to study the effect of Schroth exercise on reducing the degree of scoliosis in teenagers. Objective: To understand the effect of Schroth exercise on reducing the scoliosis curve in teenagers. Methods: a narrative review of population, interventions, comparisons, outcomes using the PICO framework. Articles were identified using 2 databases, PubMed with 791.275 article results, and Google Scholar with 22.900 article results matching keywords. Select items according to the flowchart. Results: A total of 814.175 articles from 2 databases, after screening abstract for title and relevance, 10 articles were identified based on inclusion and exclusion criteria, and 10 articles demonstrated the effect of Schroth exercise on curvature reduction in teenagers who exercises over 2 weeks 3 times/week and 5 times 60 minutes exercise. Conclusion: Training Schroth exercise can reduce the scoliosis curve in teenagers.